Bifidobacteria exert strain-specific effects on stress-related behavior and physiology in BALB/c mice. - Savignac, H; Kiely, B; Dinan, T; Cryan, J (Blackwell Publishing Ltd, 2014)
BACKGROUND: Accumulating evidence suggests that commensal bacteria consumption has the potential to have a positive impact on stress-related psychiatric disorders. However, the specific bacteria influencing behaviors related to anxiety and depression remain unclear. To this end, we compared the effects of two different Bifidobacteria on anxiety and depression-like behavior; an antidepressant was also used as a comparator. METHODS: Innately anxious BALB/c mice received daily Bifidobacterium longum (B.) 1714, B. breve 1205, the antidepressant escitalopram or vehicle treatment for 6 weeks. Behavior was assessed in stress-induced hyperthermia test, marble burying, elevated plus maze, open field, tail suspension test, and forced swim test. Physiological responses to acute stress were also assessed. KEY RESULTS: Both Bifidobacteria and escitalopram reduced anxiety in the marble burying test; however, only B. longum 1714 decreased stress-induced hyperthermia. B. breve 1205 induced lower anxiety in the elevated plus maze whereas B. longum 1714 induced antidepressant-like behavior in the tail suspension test. However, there was no difference in corticosterone levels between groups. CONCLUSIONS and INFERENCES: These data show that these two Bifidobacteria strains reduced anxiety in an anxious mouse strain. These results also suggest that each bacterial strain has intrinsic effects and may be beneficially specific for a given disorder. These findings strengthen the role of gut microbiota supplementation as psychobiotic-based strategies for stress-related brain-gut axis disorders, opening new avenues in the field of neurogastroenterology.